The Development of an English Achievement Test at a Private Senior High School in Manado - Mogi, Amelia Cindy; Sinadia, Alfrits Roul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2023)
This research was conducted due to the unavailability of teacher-made tests developed based on the principles of developing quality tests for use in schools. This study aims to analyze the quality of a Grade X English test items developed together with an English teacher at a private high school in Manado City, North Sulawesi. The developed test was intended to measure student achievement in the middle of the semester or called the midterm exam. The test consisted of 50 multiple-choice items that were tested on 133 Grade X students at the school. The results of the analysis show the quality of each item in terms of difficulty, discriminating power, and effectiveness of distractors. The final evaluation results on the quality of each item showed that, out of 50 items, there were only 11 items that met the category of qualified item difficulty level and differentiating power. Some items have one, two, or three distractors that do not function properly or are ineffective for their function as distractors. For this reason, all ineffective distractors must be corrected so that the items can be used to measure student achievement. Keywords— test item analysis, test item quality, item difficulty, item discrimination power, distractor effectiveness Penelitian ini dilakukan karena tidak tersedianya tes buatan guru yang dikembangkan berdasarkan prinsip-prinsip pengembangan tes yang berkualitas untuk digunakan di sekolah. Penelitian ini bertujuan untuk menganalisis kualitas butir soal mata pelajaran bahasa Inggris Kelas X yang dikembangkan bersama dengan guru bahasa Inggris di sebuah SMA swasta di Kota Manado, Sulawesi Utara. sekolah. Tes yang dikembangkan merupakan tes yang diperuntukkan untuk mengukur prestasi belajar siswa di tengah semester atau ujian tengah semester. Tes ini terdiri dari 50 butir pilihan ganda yang diujicobakan kepada 133 siswa Kelas X di sekolah tersebut. Hasil analisis kualitas butir soal menunjukkan kualitas setiap butir dalam hal tingkat kesukaran, daya pembeda, dan efektivitas distraktor. Hasil evaluasi akhir mengenai kualitas setiap butir menunjukkan bahwa dari 50 butir soal hanya terdapat 11 butir yang memenuhi kategori tingkat kesukaran dan daya pembeda yang baik. Beberapa butir soal memiliki satu, dua, atau tiga distraktor yang tidak berfungsi dengan baik atau tidak efektif untuk fungsinya sebagai pengecoh. Untuk itu, semua distraktor yang tidak efektif harus diperbaiki agar butir soal tersebut dapat digunakan untuk mengukur prestasi siswa. Kata kunci— analisis butir soal, kualitas butir soal, tingkat kesukaran butir, daya pembeda butir, efektivitas distraktor